Analysis of the Application of Information and Communication Technologies by Undergraduates during Distance Learning under the Quarantine Restrictions - Oleh Sukhovirskyi (Pedagogical Discourse, 2020)
The article analyses the results of the survey of undergraduates of specialities 073 Management and 011 Educational, Pedagogical Sciences on their attitude to distance learning and the structure of application of ICT under the quarantine restrictions. It is found out that at the beginning of the quarantine, most undergraduates had a high or medium level of computer skills. The beginning of distance learning motivated the undergraduates to master new tools and technologies, which significantly increased the level of their skills. The list of software and Internet resources used in the educational process was mainly determined by the conditions of organization of classes and teachers. The most popular tools were Internet search, video conferencing and distance learning platforms, and instant messaging systems. Self-confidence, high initial level of computer skills determined the overall positive dynamics of the attitude to the use of ICT in the educational process. Also, the vast majority of undergraduates were satisfied with the introduction of distance learning both at the beginning of quarantine and after its completion. At the same time, the main obstacles that undergraduates meet in the educational process using ICT have been identified. These include lack of computer equipment, limited access to high-speed Internet, lack of skills, and problems with the use of applied software. It is found out that the level of workload during the distance learning is quite high. Taking into account the fact that the significant number of undergraduates work in parallel with their studies, in particular in educational institutions, the duration of the use of ICT tools can sometimes exceed 10 hours a day. However, this overload do not preclude the additional use of such means for entertainment. The introduction of quarantine encouraged undergraduates to study independently and learn new tools. Most of them note the acquisition of new skills related to the use of video conferencing, distance learning platforms and online courses.